Finding the organization in the communication: discourse as action and sensemaking - Taylor, James R.; Robichand, Daniel (2004)
This article discusses two ways in which language and discourse have entered conception of organizing: as communicative activities of agents (conversations); and as discursively based interpretations defining agents, purposes, and organizations (texts). Conversation, framed within a material/social and a language environment, is the site where organizing occurs and where agency and text are generated. As text, in turn, the language environment frames conversations and reflects the sensemaking practices and habits of interpretation of organization members dealing with their immediate material/social purposes. Using a senior management meeting as an illustration, the article discusses these two levels of apprehension of the language-organization relationship and argues that a dynamic view of language and organizing must account for the processes linking both sides of the organization-language relationship. - Reproduced.
Keywords: Organizations